Transferências federais e equilíbrio federativo: um estudo da evolução dos estados e df brasileiros no período de 2007-2014 - OLIVEIRA, Mariana Aguiar de (2016)
This master‟s degree dissertation is characterized as an applied research with quantitative approach based on statistical and interpretative procedures. The origin of the data is documental and it‟s collection was made over the internet with cross section evaluating the same variables over the years 2007 to 2014, describing their behavior and performing statistical correlations between them. It is intended to study if, in Brazil, the federal transfers to States and to the Federal District are fulfilling their primary purpose of existence in federations, which is: reducing heterogeneity/ regional disparities in order to make the federal entities more equalized for the provision of public services within a minimum national level. The chosen public services are health and education, given their importance in the country‟s democratization process in the 1980s, with the Constituent Assembly of 1987 and the Federal Constitution of 1988. The research can be divided in three stages: 1) collection of the transfer values in order to determine which Federal Entities are receiving more or fewer resources. Then, it was calculated the per capita revenue, which measures the total revenue received by the Federal Entity‟s Treasury, including the transfers, and this variable will be correlated with health and education indicators; 2) collection of health and educational indicators, provided by official government websites; and, 3) statistical correlation between the per capita revenue variable and health and education indicators. According to the results, in terms of destination of the transfers, it was detected that the poorest regions have been receiving more mandatory transfers, but also that these transfers have not been enough to equalize the Federal Entities. When correlating the per capita revenue variable and health and education indicators, it was verified that the Entities that receive more mandatory transfers not necessarily have a better performance in the provision of these public services. Instead, Federal Entities with higher levels of mandatory transfers in their budgets (remembering that theses transfers were not enough to equalize the Entities) and lower per capita revenue, in other words, without other sources of revenues, showed no indication of a minimum national uniformity tendency in the provision of these public services. Thus, in Brazil, focusing the mandatory transfers to the poorest regions, like the way it has been done, does not contribute to the reduction of the heterogeneities.